THE INFLUENCE OF PROFITABILITY, LIQUIDITY AND INFLATION ON DIVIDEND POLICY IN PRIMARY CONSUMER SECTOR COMPANIES ON THE INDONESIAN STOCK EXCHANGE - Rafi Aldarma; Wahyudi Wahyudi (Jurnal Manajemen, 2023)
Abstract: This research is a quantitative study that aims to determine the effect of profitability, liquidity and inflation on dividend policy in primary consumen sector companies listed on the Indonesia Stock Exchange in 2019 - 2022. This study used 26 companies as samples with purposive sampling method. The method used is Panel Data Regression Analysis and Moderate Regression Analysis (MRA) with the E-Views 12 program. The results of this study indicate that (1) Profitability effects dividend policy, (2) liquidity has no effect on dividend policy, (3) inflation has no effect on dividend policy. Keywords : Dividend Policy; Profitability; Liquidity; Inflation